A case of incarcerated gravid uterus with a history of cesarean section was a good candidate for manual reduction: A case report. Issue 1 (12th November 2020) - Suzuki, Sayaka; Obata, Soichiro; Utsunomiya, Mariko; Miyagi, Etsuko; Aoki, Shigeru
Abstract: Because the anterior lower uterine segment is stretched, the incarcerated gravid uterus case with a history of cesarean section is a good candidate for manual reduction. Abstract : Because the anterior lower uterine segment is stretched, the incarcerated gravid uterus case with a history of cesarean section is a good candidate for manual reduction.